AN ANALYSIS OF ILLOCUTIONARY ACTS AS FOUND IN JANE AUSTEN’S MANSFIELD PARK - Andi Jaihutan Silitonga (LPPM Universitas Darma Agung, 2018)
This researchentitled An Analysis of illocutionary Acts as Found in Jane Austen's Mansfield Parkwhich dealing with theexpressive illocutionary acts as the analysis of pragmatics on novel utterances. The objective of this analysis was to prove that the expressive illocutionary couldalso be applied in literature, especially to find out the types, the dominant types and the reason of the most dominantly expressive illocutionary act in Jane Austen’s Mansfield Park. This research was conducted by using qualitative and quantitative method. The data were taken from all the evenchapters in the novel. The result showed that there were 140 expressive illocutionary acts. They were found in the novel with the classification as follows: expressive for thanks 12 (8.58%), expressive for apologies 9 (6.43%), expressive for congratulations 16 (11.43 %), expressive for greetings 5 ​​(3.57%), expressive for wishes 30 (21.43%), expressive for attitudes 68 (48.57%). The most dominant classification of expressive illocutionary acts was expressives for attitudes68 (48.57%). The reason of this type of dominant expressive for attitudes in Jane Austen's Mansfield Park because it recounts the daily conversation and conveys what the author believes. It means that the author of the novel makes all the utterances in a novel based on assumptions, her feelings and her experiences, so all of the utterances are mostly used to criticize, denounce and complain expression for attitudes.